Patient-Centered Structured Interdisciplinary Bedside Rounds in the Medical ICU - Cao, Victor; Tan, Laren D; Horn, Femke; Bland, David; Giri, Paresh; Maken, Kanwaljeet; Cho, Nam; Scott, Loreen; Dinh, Vi A; Hidalgo, Derrek; Nguyen, H Bryant (Critical care medicine, 2018)
We examined the effects of introducing patient-centered structured interdisciplinary bedside rounds in the medical ICU with respect to rounding efficiency, provider satisfaction, and patient/family satisfaction. A prospective, nonblinded, nonrandomized, parallel group study from June 21, 2016, to August 15, 2016. The medical ICU at a tertiary care academic medical center. A consecutive sample of adult patients, family members, and healthcare providers. The patients and healthcare providers were arbitrarily assigned to either the patient-centered structured interdisciplinary bedside rounds or nonstructured interdisciplinary bedside round care team. Healthcare providers on the patient-centered structured interdisciplinary bedside rounds team were educated about their respective roles and the information they were expected to discuss on rounds each day. Rounds completion data and satisfaction questionnaires from healthcare providers, patients, and family members were obtained from both patient-centered structured interdisciplinary bedside rounds and nonstructured interdisciplinary bedside round teams. Data were obtained from 367 patient-centered structured interdisciplinary bedside rounds and 298 nonstructured interdisciplinary bedside round patient encounters. Family members were present during 31.1% rounding encounters on the patient-centered structured interdisciplinary bedside rounds team and 10.1% encounters on the nonstructured interdisciplinary bedside round team (p < 0.01). Total rounding and interruption times were significantly shorter on patient-centered structured interdisciplinary bedside rounds compared with nonstructured interdisciplinary bedside round patients, 16.9 ± 10.0 versus 22.4 ± 14.9 and 2.0 ± 2.2 versus 3.9 ± 5.5 minutes, respectively (both p < 0.01). Mechanical ventilation, patient-centered structured interdisciplinary bedside rounds, and attending style independently contributed to the earlier completion of rounds (all p < 0.01). Surveys of 338 healthcare provider encounters on the patient-centered structured interdisciplinary bedside rounds team compared with 301 nonstructured interdisciplinary bedside round encounters showed perceptions of improved communication of patient management plans, increased input from the entire team, and clarity on task assignments (all p < 0.05). The attending physicians provided teaching points on 51.2% of patient-centered structured interdisciplinary bedside rounds compared with 33.9% of nonstructured interdisciplinary bedside round patient encounters (p < 0.01). For the patients and family members surveyed, 38 patient-centered structured interdisciplinary bedside rounds, and 30 nonstructured interdisciplinary bedside round, there were no differences in measures of satisfaction. Patient-centered structured interdisciplinary bedside rounds provide a venue for increased rounding efficiency, provider satisfaction, and consistent teaching, without impacting patient/family perception.